The effect of stress incontinence operations on sexual functions: Laparoscopic burch versus transvaginal Tape-O - İlknur Gumus; Muberra Namli Kalem; Ziya Kalem; Onder Surgit; Aydın Köşüş (Wolters Kluwer Medknow Publications, 2018)
Aim: Stress urinary incontinence (SUI) has some negative emotional and physical effects on sexual functions. In this study, we aimed to question the effects of surgical treatment of stress incontinence on sexual function using the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) form. Materials and Methods: A total of 77 sexually active women who were surgically treated for SUI between 2014 and 2015 at a university hospital. Tension-free transvaginal tape (TVT-O) operation and the laparoscopic Burch procedure were performed on 42 and 35 patients, respectively. Patients with isolated stress incontinence were included in this study. All patients enrolled were invited to fill out the PISQ-12 questionnaire before surgery and 6 months after surgery. Results: The mean total postoperative PISQ-12 score in both TVT-O and Burch groups was significantly increased compared to the preoperative period (P < 0.001 and P < 0.001, respectively). When the PISQ-12 scores were evaluated according to the subgroups, physical and partner-dependent scores significantly increased in the postoperative period compared to the preoperative period in the TVT-O group (P < 0.001 and P = 0.004, respectively). Conclusions: Rate of the surgery success for SUI is positively correlated with the improvement of sexual functions. Minimally invasive methods in SUI surgery has been progressively increasing day-by-day. The lesser invasive approaches seem to replace the more invasive approaches in the near future.